E-Nutrition Label: Design and Architecture of a Web-Based Front-of-Pack Nutrition Labeling System - Yulita Sirinti Pongtambing; Arni Raihanah Rahman; Eliyah Acantha Manapa Sampetoding (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
FOPNLs (Front of Pack Nutrition Labels) are nutritional labeling systems placed on the front of packaging to present nutritional information more simply. FOPNLs can help consumers quickly determine foods with better nutritional content and lower levels of salt, sugar, and fat. Nutrition labels influence consumer behavior and decision-making in determining healthy foods. However, the nutritional labeling system in Indonesia is not yet fully informative, and policies mandating that the food industry implement such labeling are not yet fully enforced. This study aims to develop an application model that automatically calculates FOPNLs for food products. The study resulted in a website prototype and limited testing, using the Design Science Research Method. DSRM can effectively bridge the theoretical foundations with practical requirements in the development of information system artifacts, particularly within the context of digital transformation in the healthcare sector. The result shows prototype functions well and can automatically calculate RDA and generate FOPNLs based on the nutritional label and serving size entered into the system. Functional evaluation using Black-Box Testing demonstrated a 100% success rate across all test scenarios, while the qualitative TAM-based assessment indicated that the proposed artifact was positively accepted, particularly regarding its perceived usefulness and ease of use. This prototype can be easily used by MSMEs that produce processed foods. Future research can be conducted through limited trials at the District or City UMKM Office.